Bidirectional regulation of lipid metabolism and the tumor microenvironment: new perspectives from mechanism to therapy - Shi, Kaixin; Pan, Bing; Zheng, Ruixin; Liu, Kaiyi; Song, Jincheng; Wang, Xiaobo; Li, Li (Frontiers in Immunology, 2025)
The role of lipid metabolism in cancer and immune regulation has received significant attention in recent years. Reprogramming of lipid metabolism is one of the key hallmarks of cancer and plays a critical role in cancer progression by supporting the rapid proliferation, survival, and metastasis of tumor cells. Importantly, beyond its well-established functions in cancer cells, lipid metabolism dynamically regulates the functions of various immune cells within the TME (e.g., T cells, natural killer cells, macrophages), thereby molding antitumor immune responses. This review combines the contemporary awareness of the reciprocal interactions between lipid metabolism and the TME. We start with a simple overview of key lipid metabolic pathways in cancer cells, followed by an in-depth exploration of the way lipid uptake, synthesis, and oxidation influence the fate and role of tumor-infiltrating immune. We also appraise the translational potential of targeting lipid metabolism and propose that combining inhibitors of key metabolic enzymes, for example fatty acid synthase or acetyl-CoA carboxylase, with immunotherapy can not only effectively alleviate immunosuppression but also overcome immunosuppression. Finally, we spotlight the remaining knowledge gaps and put forward future research priorities and potential. Intervening in lipid metabolic interactions represents a promising prospect for developing the novel cancer treatment strategies.